Implementasi Sistem Pemilihan Agen Perubahan Pada Pengadilan Militer Tinggi I Medan Menggunakan Metode Topsis - Ahmad Zakir; Febrica Hotmaulina Sitorus; Fachrul Rozi Lubis (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2023)
The Medan High Military Court I is an essential institution in Indonesia's military justice system, and change within this institution plays a crucial role in improving efficiency, accountability, and legal services. Change agents within the military justice system are crucial in improving the system, increasing accountability, and ensuring compliance with human rights principles and applicable laws. Selecting effective change agents at Medan High Military Court I using the Technique for Order Preference by Similarity to the Ideal Solution (TOPSIS) method. The TOPSIS method measures and compares change agent candidates based on predetermined criteria. These criteria included competence, experience, understanding of the military justice system, communication, and leadership ability. Data was obtained through surveys and interviews with staff and stakeholders at Medan High Military Court I. This system will assist decision-makers at Medan High Military Court I in determining the most suitable change agent to lead change in the institution. In addition, this research can also provide insights into the importance of selecting the right change agent in the context of military justice, which in turn can improve the effectiveness of the military justice system as a whole.